THE PRICE DYNAMICS OF STRATEGIC COMMODITIES DURING RAMADAN: AN ANALYSIS FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Anisa, Lina Nur (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This article discusses the dynamics of strategic commodity prices during Ramadhan from an Islamic economic perspective, highlighting the factors influencing price fluctuations and policies to address them. Based on a literature review, the study identifies that surges in demand, uneven distribution, and unfair trading practices contribute to price volatility that harms consumers. The aim of this research is to explore how Islamic economic principles, such as fair pricing and maslahah, can be applied to create a more stable and equitable market. The research methodology involves literature analysis, reviewing both primary and secondary sources to gain a comprehensive understanding of the relationship between Sharia-based pricing policies and market stability during Ramadhan. The findings show that implementing Sharia-based price policies, such as prohibitions on hoarding (ihtikar) and more equitable distribution of goods, can help reduce unreasonable price spikes. The study also underscores the importance of education and Islamic economic literacy to strengthen consumer trust and encourage more ethical decision-making by market participants. In conclusion, Sharia-based policies provide a relevant framework for managing price fluctuations of commodities during Ramadhan, creating a better balance between producers, distributors, and consumers. Thus, this study contributes to Islamic economic literature by offering a more practical and applicable approach to maintaining price stability and improving societal welfare.